Głuchoniemi czy wielojęzyczni?Problemy osób z uszkodzonym słuchem w przyswajaniu języka - Krakowiak, Kazimiera (Neofilolog, 2011)
The author aims at presenting in a synthetic way the most important prob-lems appearing in the process of language and speech acquisition and edu-cation of children with hearing impairment on the basis of contemporary knowledge of audiophonology, speech therapy and pedagogy of the deaf. The aim of the paper is to present the possibilities and ways of overcoming the difficulties in communication with such children and creating condi-tions facilitating their language acquisition and education of this group of students in the environment of integrative and mainstream school.